Covalent–Organic Frameworks: Single‐Pore versus Dual‐Pore Bipyridine‐Based Covalent–Organic Frameworks: An Insight into the Heterogeneous Catalytic Activity for Selective CH Functionalization (Small 22/2021). Issue 22 (2nd June 2021) - Vardhan, Harsh; Al‐Enizi, Abdullah M.; Nafady, Ayman; Pan, Yanxiong; Yang, Zhongyu; Gutiérrez, Humberto R.; Han, Xiaolong; Ma, Shengqian
Abstract : Transition metal catalyzed carbon—hydrogen functionalization imparts a paradigm shift in the complex target synthesis, including pharmaceutical and material science applications. To establish structure‐function‐property relationship of covalent organic frameworks, palladium docked dual‐pore COFs with controllable bipyridine content exhibit regioselective C—H to C—X (X = Cl, Br, I) and C—O functionalization, and compared with single pore framework. This protocol presented by Shengqian Ma and co‐workers (article number 2003970 ) features high efficiency, remarkable reusability, and recyclability.